Social stressors and social resources at work and their association with self-reported health complaints among ready-made garment workers in Bangladesh: a cross-sectional study - Annegret Dreher; Rita Yusuf; Hasan Ashraf; Syed A. K. Shifat Ahmed; Christian Strümpell; Adrian Loerbroks (BMC, 2022)
Abstract Background Bangladesh is one of the world's largest garment exporters. Physical working conditions of garment workers are precarious and known to largely affect their health. Research on garment workers' psychosocial working conditions, however, is scarce. We aimed to quantify psychosocial working conditions of garment workers and possible associations with workers' health. Methods We conducted a cross-sectional survey among 1,118 ready-made garment (RMG) workers in labor colonies in Dhaka, Bangladesh, in February 2021. Descriptive analyses were performed to characterize social stressors (e.g., being bullied at work, poor leadership) and social resources at work (e.g., receiving support at work, vertical trust between management and employees, beneficial leadership) and workers' health (self-reported overall health and 10 specific health complaints). To examine links of social stressors and social resources with self-reported health outcomes we ran multivariable Poisson regression models yielding prevalence ratios (PR) and 95% confidence intervals (CI). Results We found low to moderate levels of workplace bullying and high levels of poor leadership (i.e., supervisors not caring about workers' problems). We also found high levels of social support, vertical trust and beneficial leadership (i.e., supervisors taking decisions free of bias). Garment workers frequently suffered from health complaints, first and foremost headache (68.3%), cold (55.3%), and back pain (50.7%). Health outcomes were poorer among workers who reported to be bullied at work versus not bullied (e.g., PR 1.55 [95% CI 1.32-1.92] for poor self-reported health when bullied by colleagues) and health was better among those reporting to feel supported versus unsupported (e.g., PR 0.61 [0.52-0.71] for poor self-reported health when supported by supervisor). Perceived vertical trust between workers and management was weakly associated with better health. Leadership behavior did not display a consistent pattern. Conclusions Our findings suggest that working conditions of RMG workers are rather good (e.g., characterized by low levels of bullying and high levels of support, vertical trust and beneficial leadership). The majority of workers reported good or very good health, although health complaints were frequently mentioned, first and foremost headache, cold, and back pain. Associations between psychosocial working conditions and health indicate worse working conditions being associated with poorer health.